Highly Efficient and Ultrasensitive Large‐Area Flexible Photodetector Based on Perovskite Nanowires. Issue 1 (30th November 2018) - Asuo, Ivy M.; Fourmont, Paul; Ka, Ibrahima; Gedamu, Dawit; Bouzidi, Soraya; Pignolet, Alain; Nechache, Riad; Cloutier, Sylvain G.
Abstract: Hybrid organic–inorganic perovskites have shown exceptional semiconducting properties and microstructural versatility for inexpensive, solution‐processable photovoltaic and optoelectronic devices. In this work, an all‐solution‐based technique in ambient environment for highly sensitive and high‐speed flexible photodetectors using high crystal quality perovskite nanowires grown on Kapton substrate is presented. At 10 V, the optimized photodetector exhibits a responsivity as high as 0.62 A W −1, a maximum specific detectivity of 7.3 × 10 12 cm Hz 1/2 W −1, and a rise time of 227.2 µs. It also shows remarkable photocurrent stability even beyond 5000 bending cycles. Moreover, a deposition of poly(methyl methacrylate) (PMMA) as a protective layer on the perovskite yields significantly better stability under ambient air operation: the PMMA‐protected devices are stable for over 30 days. This work demonstrates a cost‐effective fabrication technique for high‐performance flexible photodetectors and opens opportunities for research advancements in broadband and large‐scale flexible perovskite‐based optoelectronic devices. Abstract : A facile and inexpensive approach for fabrication of flexible photodetectors in ambient environment using interconnected perovskite nanowires is presented. The addition of thiocyanate anions and a poly(methyl methacrylate) layer helps to fabricate stable perovskite‐based photodetectors with specific detectivity of 7.3 × 10 12 Jones, response times of 227.2 µs (rise) and 215.4 µs (decay), and remarkable photocurrent stability even beyond 5000 bending cycles.